DMPK mRNA Expression in Human Brain Tissue Throughout the Lifespan. (February 2021) - Langbehn, Kathleen E.; Carlson-Stadler, Zoe; van der Plas, Ellen; Hefti, Marco M.; Dawson, Jeffrey D.; Moser, David J.; Nopoulos, Peggy C.
Abstract : Objective: Myotonic dystrophy is a multisystem disorder caused by a trinucleotide repeat expansion on the myotonic dystrophy protein kinase ( DMPK ) gene. To determine whether wildtype DMPK expression patterns vary as a function of age, we analyzed DMPK expression in the brain from 99 donors ranging from 5 postconceptional weeks to 80 years old. Methods: We used the BrainSpan messenger RNA sequencing and the Yale Microarray data sets, which included brain tissue samples from 42 and 57 donors, respectively. Collectively, donors ranged in age from 5 postconceptional weeks to 80 years old. DMPK expression was normalized for each donor across regions available in both data sets. Restricted cubic spline linear regression models were used to analyze the effects of log-transformed age and sex on normalized DMPK expression data. Results: Age was a statistically significant predictor of normalized DMPK expression pattern in the human brain in the BrainSpan ( p < 0.005) and Yale data sets ( p < 0.005). Sex was not a significant predictor. Across both data sets, normalized wildtype DMPK expression steadily increases during fetal development, peaks around birth, and then declines to reach a nadir around age 10. Conclusions: Peak expression of DMPK coincides with a time of dynamic brain development. Abnormal brain DMPK expression due to myotonic dystrophy may have implications for early brain development.